2017
DOI: 10.1021/acs.energyfuels.6b03177
|View full text |Cite
|
Sign up to set email alerts
|

Tetraethylenepentamine-Modified Activated Semicoke for CO2 Capture from Flue Gas

Abstract: To separate CO2 from coal-fired power plant emissions, semicoke, which is cheap and easy to obtain, was further activated to use as the carrier and tetraethylenepentamine (TEPA) was impregnated in the activated semicoke to prepare solid amine sorbents. The effects of activating agents, adsorption temperature, and the presence of water on CO2 sorption were investigated in a fixed-bed reactor, and the regenerability and adsorption kinetics for prepared sorbents were also studied. The equilibrium adsorption capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 33 publications
(56 reference statements)
0
23
0
Order By: Relevance
“…For SE600-2, the equilibrium adsorption capacity was 2.14 mmol g À1 , and for SE700-2, the equilibrium adsorption capacity was 2.70 mmol g À1 , but for SE900-2, the equilibrium adsorption capacity was dropped to 1.94 mmol g À1 . According to the previous FT-IR characterization, 32 in the process of N 2 activation, the peaks of the semicoke at 1020 and 1383 cm À1 appeared, which separately representing the asymmetric stretching vibration of C-O-C in the aliphatic ether and aromatic ether. As the activation temperature increased, the pores and cracks became more developed, in which the ether groups became more abundant.…”
Section: Characterizationmentioning
confidence: 67%
See 1 more Smart Citation
“…For SE600-2, the equilibrium adsorption capacity was 2.14 mmol g À1 , and for SE700-2, the equilibrium adsorption capacity was 2.70 mmol g À1 , but for SE900-2, the equilibrium adsorption capacity was dropped to 1.94 mmol g À1 . According to the previous FT-IR characterization, 32 in the process of N 2 activation, the peaks of the semicoke at 1020 and 1383 cm À1 appeared, which separately representing the asymmetric stretching vibration of C-O-C in the aliphatic ether and aromatic ether. As the activation temperature increased, the pores and cracks became more developed, in which the ether groups became more abundant.…”
Section: Characterizationmentioning
confidence: 67%
“…According to the previous study, the semicoke activated at 700 C for 2 h suggested a typical crack-type mesoporous and macroporous structure, with mesopores centering at 20-30 nm. 32 Here, the pore structures of the semicoke activated at different temperature are shown in Table 1. Before and aer HCl treating, the BET surface area and total pore volume of the activated semicoke all rst increased and then decreased with the activation temperature increasing from 600 C to 800 C. To the semicoke activated at a same temperature, HCl treating caused the BET surface area and total pore volume increased, suggesting the reaming effect of HCl washing.…”
Section: Characterizationmentioning
confidence: 99%
“…The large energy penalty caused by the regeneration of the absorbents is challenging for absorption . Most membranes are incapable of extracting CO 2 with high purity , . Recent studies suggest that adsorption processes using porous materials are promising alternatives for CO 2 capture, including porous carbons, MOFs, polymers,, and zeolites …”
Section: Introductionmentioning
confidence: 99%
“…[5] Most membranes are incapable of extracting CO 2 with high purity. [6,7] Recent studies [8][9][10] suggest that adsorption processes using porous materials [11] are promising alternatives for CO 2 capture, including porous carbons, [12][13][14] MOFs, [15][16][17] polymers, [18,19] and zeolites. [20][21][22][23] Porous carbons such as carbon aerogels have received much attention for their extensive applicability as CO 2 adsorbents due to their special pore structure, variable surface properties, high thermal stability and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Original Research Article: Hybrid system for CO 2 capture power plant system can meet the CO 2 removal requirements. In a coal-fired power plant, the methods generally applied for carbon capture are cryogenic distillation, adsorption separation, 9,10 membrane separation, [11][12][13] chemical absorption, 14,15 etc.…”
Section: Introductionmentioning
confidence: 99%